The Role Of Lifelong Learning In Mediating The Effect Of Organizational Justice On Lecturer Engagement In Private Universities - Rasyid, Rohsita Amalyah; Syaifuddin, Dedy Takdir; Aliddin, Laode Asfahyadin; Masri, Muhamad (Journal of Neonatal Surgery, 2025)
This study aims to examine and analyze the influence of organizational justice on lecturer engagement, as well as to examine the mediating role of lifelong learning in the relationship. The focus of this study is lecturers at private universities in Mamuju Regency, a developing area facing the challenge of limited resources. This study uses a quantitative approach by collecting data through questionnaires distributed to permanent lecturers in two PTS totaling 165 permanent lecturers with proportional convenience sampling techniques. The analysis technique uses Structural Equation Modeling (SEM-PLS). The results of the study indicate that organizational justice has a positive and significant effect on lifelong learning and lecturer engagement. Then lifelong learning affects lecturer engagement. In addition, lifelong learning is proven to significantly mediate the influence of organizational justice on lecturer engagement. These findings emphasize the importance of creating a fair work environment and supporting continuous learning to improve the quality of the tridharma of higher education